Limit theorems in the metric spaces L1 and l1 - Bikelis, A.; Jasiūnas, H. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Бикялис, Г. Ясюнас. О предельных теоремах в метрике пространства L1 и l1A. Bikelis, H. Jasiūnas. Ribinės teoremos erdvės L1 ir l1 metrikoje